Heading to Reciprocity in Islamic Psychology: Coping Adaptive Strategy for Family Resilience During the Pandemic - Gumiandari, Septi; Abd. Madjid; Eti Nurhayati; Listiani, Wanda; Ilman Nafi’a (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
This study aimed to analyze the factors contributing to family economic resilience in Muslim communities and introduce the mubadalah concept as a reciprocal thinking paradigm to enrich family practices and comprehension for achieving robust economic resilience. Conducting a mixed-methods approach involving interviews and questionnaires, the findings of the research highlight the interconnectedness between robust family economic resilience and the active engagement of all family members, particularly spouses, in fortifying economic stability. The study emphasizes the significance of comprehensive religious understanding to foster balanced and mutually beneficial relationships within the family. The introduction of the concept of mubadalah serves as a reciprocal thinking paradigm, highlighting interdependence and mutual benefit, particularly within the family context guided by Islamic values. The research concludes that comprehensive religious understanding, a balanced gender perspective, and an adaptive family organizational structure are key factors in building family economic resilience. In situations where families lack comprehensive religious knowledge, economic challenges and difficulties in sharing adaptive roles between husbands and wives may arise. Consequently, the research advocates for a more balanced and mutually beneficial understanding in interpreting Islamic teachings, intending to achieve a more equitable comprehension and prevent biased interpretations that could lead to disparities.